Autoinflammatory diseases: what is behind them and what is new? - Maalouly, Michele; Saade, Serena; Kurban, Mazen (Dermatology Reports, 2022)
Autoinflammatory diseases are characterized by bouts of systemic or localized inflammation in the absence of an infection. While some autoinflammatory diseases are caused by a single gene mutation, others have been shown to be multifactorial, involving a large array of genes coupled with environmental factors. Previous studies briefly elucidated the molecular mechanisms behind the many autoinflammatory diseases, focusing on the dysregulation of interleukin (IL)-1β or IL-18, nuclear factor- κB activation, and Interferons secretion. In this review, we precisely highlight the autoinflammatory disease-specific signalosomes, and we aim to provide a scaffold of the link between the various affected pathways.